THE ROLE OF SOCIAL SUPPORT IN MANAGING STRESS AMONG GENERATION Z IN BANDUNG - Sakroni, Sakroni (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study aims to explore the role of social support in managing stress among Generation Z in Bandung. Using a quantitative approach, the research involved 300 respondents aged between 12 and 27 years. Data were collected through a questionnaire measuring social support and stress levels. The results indicate that social support, particularly emotional support from family and close friends, as well as informational support from the internet and social media, significantly impacts stress reduction. Correlation analysis revealed a significant negative relationship between social support and stress levels (r = -0.45, p < 0.01), while regression analysis showed that social support significantly affects stress levels (β = -0.35, p < 0.01). Stress levels also varied by age group, with the 12-17 age group reporting higher stress levels. The study suggests enhancing family support, utilizing technology for social support, and developing support programs in schools and universities as measures to improve mental well-being among Generation Z.